Soil-structure interaction effects on the seismic performance of steel moment-resisting frames equipped with optimal rotational friction dampers. (September 2022) - Jarrahi, H.; Asadi, A.; Khatibinia, M.; Etedali, S.; Paknehad, S.
Abstract: This study investigate the soil-structure interaction (SSI) effects on the seismic performance of steel moment-resisting frames (SMRF) equipped with optimal rotational friction dampers (RFDs). Firstly, a simultaneous optimal design based on the energy concepts is expanded to find the optimal placement and the corresponding optimal parameters of the RFDs for the seismic protection of a nonlinear six-story SMRF. Then, the direct method is adopted to simulate the nonlinear SSI effects on the optimal RFDs-equipped SMRF. The input, hysteretic, dissipated energies and the drift of stories of the controlled SMRF subjected to four real earthquake excitations indicate that SSI can considerably influence the seismic performance of the controlled SMRF. Nevertheless, the significant amount of the seismic input energy is dissipated by optimal RFDs and therefore its limited amount is dissipated by the structural. Moreover, the optimal RFDs can maintain the story drift ratios within the acceptable drift limits.